2008
DOI: 10.2166/wst.2008.500
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and drawbacks of thermal pre-hydrolysis for operational performance of wastewater treatment plants

Abstract: This paper presents benefits and potential drawbacks of thermal pre-hydrolysis of sewage sludge from an operator's prospective. The innovative continuous Thermo-Pressure-Hydrolysis Process (TDH) has been tested in full-scale at Zirl wastewater treatment plant (WWTP), Austria, and its influence on sludge digestion and dewatering has been evaluated. A mathematical plant-wide model with application of the IWA Activated Sludge Model No.1 (ASM1) and the Anaerobic Digestion Model No.1 (ADM1) has been used for a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Producing Class A biosolids, as defined by the USEPA, provides more diverse disposal options (USEPA, 1999). Several studies have shown that the increase in biogas production could be sufficient to preheat the WAS and heat the anaerobic digesters (Bougrier et al, 2007;Phothilangka et al, 2008;Gurieff et al, 2011). The high temperatures are typically applied by heat exchangers or steam injection (Climent et al, 2007).…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Producing Class A biosolids, as defined by the USEPA, provides more diverse disposal options (USEPA, 1999). Several studies have shown that the increase in biogas production could be sufficient to preheat the WAS and heat the anaerobic digesters (Bougrier et al, 2007;Phothilangka et al, 2008;Gurieff et al, 2011). The high temperatures are typically applied by heat exchangers or steam injection (Climent et al, 2007).…”
Section: Objectivesmentioning
confidence: 99%
“…Therefore a change in the measured concentration of non-biodegradable particulate COD could be due to a change in the concentration of X i or Z e or both. Phothilangka et al (2008) considered the transformation of Z e to bCOD but did not consider the transformation of X i to bCOD. Ramdani et al (2010) have shown that the COD fractionation of activated sludge is substantially simplified when the system is fed with a synthetic soluble biodegradable substrate such as acetate.…”
Section: Existing Pretreatment Modelsmentioning
confidence: 99%
“…Research shows that thermal hydrolysis increases biogas production by 75-80% and enzymic hydrolysis by 30% compared to AD [15]. A study into thermal hydrolysis showed an increase in biogas production by 155% [16].…”
Section: Adoption Of Advanced Anaerobic Digestionmentioning
confidence: 99%
“…The project is estimated to save US$20 million/year from the energy it produces, diversion of biosolids for use in agriculture rather than disposal, and avoidance of the use of lime (Brown andCaldwell 2010, Menco 2012). One study suggests that the thermo--pressure--hydrolysis process has the potential to reduce biosolids disposal costs by 25% (Phothilangka, Schoen and Wett, 2008).…”
Section: Cost (And/or Payback Time)mentioning
confidence: 99%